Two Liberibacter Proteins Combine to Suppress Critical Innate Immune Defenses in Citrus - Basu, Supratim; Huynh, Loan; Zhang, Shujian; Rabara, Roel; Nguyen, Hau; Velásquez Guzmán, Jeanette; Hao, Guixia; Miles, Godfrey; Shi, Qingchun; Stover, Ed; Gupta, Goutam (Frontiers in Plant Science, 2022)
We adopted a systems-based approach to determine the role of two CLas proteins, LasP235 and Effector 3, in HLB pathogenesis. While published work suggests the involvement of these CLas proteins HLB pathogenesis, the exact structure-based mechanism of their action has not been elucidated. We conducted the following experiments to determine the structure-based mechanisms of action. First, we immunoprecipitated the interacting citrus protein partners of LasP235 and Effector 3 from the healthy and CLas-infected Hamlin extracts and identified them by LC-MS/MS. Second, we performed a split GFP assay in tobacco to validate that the interactions observed in vitro are also retained in-planta. The notable in planta citrus targets of LasP235 and Effector3 include citrus innate immune proteins. Third, in vitro and in planta studies were performed to show that LasP235 and Effector 3 interact with and inhibit the functions of multiple citrus proteins belonging to the innate immune pathways. These inhibitory interactions led to a high level of reactive oxygen species (ROS), blocking of bactericidal lipid binding protein (LTP), and induction of premature programmed cell death (PCD), all of which are beneficial to CLas lifecycle and HLB pathogenesis. Finally, we performed molecular dynamics simulations to visualize the interactions of LasP235 and Effector 3 respectively with lipid transfer protein (LTP) and Kunitz protease inhibitor (KPI). This led to the design of an LTP mimic, which sequestered and blocked LasP235 and rescued the bactericidal activity of LTP thereby proving that LasP235, indeed, participates in HLB pathogenesis.